REVITALISASI LITERASI PEMANFAATAN ASET WAKAF PRODUKTIF TERHADAP NAZHIR MELALUI EDUKASI DAN DISEMINASI BUKU MANAJEMEN ASET WAKAF - Midesia, Shelly; 'Ula, Tajul 'Ula (Jurnal Pengabdian Masyarakat Polmanbabel, 2024)
Literacy problems regarding the use of productive waqf assets are still minimal at the waqf manager level in Paya Bujok Teungoh village, West Langsa District, Langsa City. Community waqf literacy is still low where people only know waqf is limited to its use for houses of worship, education and burial places. Professionalism of nazhir (waqf asset manager) where most waqf managers are still individual nazhirs or institutions that are extensions of the amil zakat institution. The competency of nazhir, the majority of whom come from amil zakat institutions, must be improved, especially regarding the skills needed in managing waqf assets, such as entrepreneurship or investment managers (asset management), so that professionalism can be formed among nazhir (waqf asset managers). Nazir also needs to look at opportunities that can improve the economic prosperity of local communities in the Waqf Ecosystem. Village policies regarding waqf, for example provisions if there are individuals or community groups who want to donate their assets, can also do so by giving (transfer) by way of gift, sale and purchase and inheritance. The dedication carried out aims to solve literacy problems regarding the use of productive waqf assets that are still minimal at the Nazhir level in Paya Bujok Teungoh Village, West Langsa District, Langsa City. The methodology used in this service is carried out with an Asset Based for Community Development (ABCD) approach where this method is very relevant to the problems faced, namely related to nazhir literacy in terms of waqf asset management in Paya Bujok Teungoh Village, Langsa City. This ABC method is an effort to increase community assets, in this case waqf assets that are already owned through increasing productive waqf literacy. After carrying out service to nazhir and waqf asset managers, PKM participants understand the concept of waqf as the sacrifice of property or assets for social purposes and public good and waqf is not just a donation, but a permanent transfer of asset ownership for a specific purpose. Participants also understand that knowledge about the types of waqf is adequate, including various types of waqf, such as productive waqf, agricultural productive waqf, educational productive waqf, and so on. This is important so that participants can choose the type of endowment that suits their goals and vision. PKM participants already have knowledge about waqf management, managing waqf assets well. This includes an understanding of the investment, care, and use of waqf proceeds to achieve desired social and economic goals.